A Preliminary Study Strategy on Development of Personalized Education Tool Using Joint Requirement Planning Technique - Fadhla Binti Junus; Nur Andula (Universitas Negeri Makassar, 2018)
Involving a number of the prospective system user and applying various techniques to discover user requirements are fundamental in software engineering. This paper briefly reports upon the inceptive phase of software development life cycle (SDLC) that aimed to assemble potential user’s recommendation in developing educational purposed application for the mobile system. The conducted study implemented Joint Requirement Planning (JRP) technique to substitute individual interview which spends a huge effort in time and cost. This small-scale research entangled 45 students of Vocational Information Technology at State Islamic University Ar-Raniry Banda Aceh Indonesia, whose acquaintance with both software engineering and pedagogical knowledge. They were entreated in observing eight selected applications that exist on the market. The software packages were utilized as a role model for developing a future personalized education tool (PET) system. The students’ experience during JRP session then were qualitatively analyzed using QDA Miner to draw a recommendation for creating a better personal learning software. This study found that the explored applications were insufficient to fulfill students’ needs, therefore the main outcome of this research expounds user requirements that will be used to design a better tool in supporting formal learning i.e. variety learning activities, incomplex navigation, and adaptable system.